Cu-Ni-Al-BASED COPPER ALLOY PLATE, METHOD FOR PRODUCING THE SAME, ELECTRONIC APPARATUS COMPONENT, CONDUCTIVE SPRING MEMBER AND SPRING MEMBER FOR AUTOFOCUS CAMERA MODULES
By optimizing the manufacturing process to enhance the number density of ultrafine precipitates and Cu concentration gradient in Cu-Ni-Al copper alloys, the material achieves significant heat resistance and strength, addressing the softening issue at high temperatures.
Patent Information
- Application Number
- JP2023122317
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
Conventional Cu-Ni-Al copper alloy sheet materials soften rapidly when exposed to high temperatures, limiting their use in applications requiring heat resistance, such as electronic equipment components and components subjected to heat from brazing or welding.
The manufacturing process involves controlling the conditions of hot rolling, intermediate cold rolling, solution treatment, aging treatment, and final cold rolling to achieve a high number density of ultrafine precipitates with a specific Cu concentration gradient near the matrix/precipitate interface, ensuring high strength and improved heat resistance.
The resulting Cu-Ni-Al copper alloy sheet material maintains 80% Vickers hardness at temperatures up to 600°C or higher, providing enhanced heat resistance and strength suitable for electronic equipment components.
Smart Images

Figure 2025018531000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cu-Ni-Al-based copper alloy sheet material having improved heat resistance and a manufacturing method thereof, and also to an electronic device part, a conductive spring member, and a spring member for an autofocus camera module, each using the sheet material. [Background technology]
[0002] Cu-Ni-Al copper alloys can be strengthened by Ni-Al precipitates, and have a metallic appearance close to white silver among copper alloys. Copper alloys with this composition are useful for electronic equipment parts such as conductive spring parts such as lead frames, connectors, and leaf springs for autofocus camera modules, as well as non-magnetic high-strength parts.
[0003] Various studies have been conducted to date on improving the other properties of Cu-Ni-Al alloys while taking advantage of their high strength properties. For example, Patent Document 1 discloses a manufacturing technology for a Cu-Ni-Al-based copper alloy plate material with excellent etching properties. In the manufacturing process, rapid heating is performed during solution treatment, cold rolling is performed after aging treatment, and then a finishing heat treatment is performed so that the heating rate is not excessive. This results in a structure with a large KAM value, and a highly smooth etched surface is obtained.
[0004] Patent Document 2 discloses a technology for manufacturing a Cu-Ni-Al-based copper alloy plate material that has an excellent "strength-bending workability balance" and excellent discoloration resistance. In the manufacturing process, a method is adopted in which a material that has been subjected to a solution treatment is given cold rolling strain as necessary, and then a first aging treatment at a higher temperature range and a second aging treatment at a conventionally common temperature range are successively performed. This two-stage aging treatment makes it difficult for discontinuous precipitation of grain boundary reaction to occur, and sufficient intragranular precipitation of fine second phase particles that contribute to strength improvement occurs, thereby achieving an excellent balance between strength and bending workability.
[0005] Patent Document 3 discloses a technology for manufacturing a sheet material having a high Young's modulus in a Cu-Ni-Al-based copper alloy. Specifically, a specific crystal orientation is obtained by performing cold rolling with intermediate annealing under specific conditions, performing solution treatment at a slow heating rate, and performing finish cold rolling under conditions where the rolling reduction ratio is controlled to be low, followed by aging treatment, thereby realizing a high Young's modulus.
[0006] Patent Document 4 discloses a manufacturing technology for a Cu-Ni-Al-based copper alloy sheet material that has excellent performance in suppressing the generation of smut during etching. In the manufacturing process, the cooling rate in the high temperature range of 900 to 700°C is controlled within a narrow range during the cooling process after solution treatment, and the cooling rate is slow at 400 to 300°C during the cooling process after aging treatment. This increases the concentration of Cu present in the Ni-Al-based precipitates more than usual, suppressing the generation of smut during etching.
[0007] Patent Document 5 discloses a manufacturing technique for a plate material that is effective in improving the etching rate in a Cu-Ni-Al-based copper alloy. In the manufacturing process, heating is performed with a predetermined tension applied in a solution treatment, and the average heating rate of 300 to 400°C during the temperature rise process in the subsequent aging treatment is set to 40°C / h or more, and the final cold rolling has a pass schedule including four or more rolling passes with a rolling reduction rate of 12% or more per pass, and the final heat treatment is performed with a rolling rate of 70 to 150 N / mm 2 The manufacturing conditions used are heating with tension of 1000 nm, which increases the order of the Ni-Al precipitates and also increases the crystal orientation of the Ni-Al precipitates relative to the rolled surface, resulting in a structure that is aligned in a certain direction, improving the etching speed. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2019-2042 A [Patent Document 2] JP 2020-50923 A [Patent Document 3] JP 2020-79436 A [Patent Document 4] Patent Publication No. 2022-27545 [Patent Document 5] JP 2022-115695 A Summary of the Invention [Problem to be solved by the invention]
[0009] Electronic equipment parts such as leaf springs for autofocus camera modules and conductive spring members such as connectors may be subjected to heat treatment for the purpose of removing distortion during part processing. They may also be incorporated into parts that are subject to heat from brazing or welding. They are also expected to be used in parts that are exposed to high temperatures during use. Conventional Cu-Ni-Al copper alloy sheet materials are rapidly softened when subjected to a thermal history of heating to a high temperature range exceeding 500°C, and the Vickers hardness after heating to, for example, 600°C is softened to a level that is significantly lower than 80% of the Vickers hardness of the sheet material before the thermal history is applied. Therefore, there may be temperature restrictions in part processing, device assembly, or usage environment, and it is desirable to improve the heat resistance of Cu-Ni-Al copper alloy sheet materials. Conventional manufacturing techniques such as those disclosed in the above-mentioned patent documents are not intended to significantly improve heat resistance.
[0010] An object of the present invention is to provide a Cu-Ni-Al based copper alloy sheet material having high strength and excellent heat resistance. [Means for solving the problem]
[0011] In Cu-Ni-Al based copper alloys, Ni 3Ni-Al-based precipitates, mainly composed of intermetallic compounds with an Al-type structure, are generated during the manufacture of the sheet material. Cu atoms are also present in the particles of the Ni-Al-based precipitates. In this specification, Ni-Al-based precipitates with a particle size of 50 nm or less, which contribute greatly to high strength, are called "fine precipitates". Furthermore, among the fine precipitates, precipitates with a particle size in the range of 10 to 20 nm are called "ultrafine precipitates". As a result of research, the inventors have found that in order to improve the heat resistance of Cu-Ni-Al-based copper alloy sheet material, (i) a high number density of ultrafine precipitates, and (ii) a small Cu concentration gradient near the interface in the atomic concentration profile of the three elements Cu, Ni, and Al that perpendicularly penetrate the interface between the parent phase and the fine precipitates, are extremely effective. It was also confirmed that the structural states (i) and (ii) can be stably realized by strictly controlling the conditions of hot rolling, intermediate cold rolling, solution treatment, aging treatment, final cold rolling, and final heat treatment. The present invention is based on these findings. The present specification discloses the following inventions.
[0012] [1] In mass%, Ni: 10.0~30.0%, Al: 1.00~6.50%, Ag: 0~0.50%, B: 0~0.15%, Be: 0~0.20%, Co: 0~2. 00%, Cr:0~0.50%, Fe:0~2.00%, Ga:0~0.50%, Ge:0~0.50%, In:0~0.50%, Mg:0~0.80%, Mn:0~ The alloy has a chemical composition consisting of 2.00%, Nb: 0-0.50%, P: 0-0.20%, Si: 0-1.00%, Sn: 0-2.00%, Ti: 0-2.00%, Zn: 0-2.00%, Zr: 0-0.40%, and the balance being Cu and unavoidable impurities, and satisfies the following formula (1); and the number density of ultrafine precipitates having a particle diameter of 10-20 nm is 1.0×10 8 pieces / mm 2 In the atomic concentration profile of the three elements Cu, Ni, and Al that perpendicularly penetrates the interface between the parent phase (region where the Al concentration is less than 10 atomic %) and fine precipitates (region where the Al concentration is more than 10 atomic %) with a particle size of 50 nm or less by 3D atom probe analysis, the position where the Al concentration is 10 atomic % is defined as the "interface position", and the Cu concentration is the median Cu concentration C 0When the position where (atomic %) is defined as the "Cu concentration median position", the Cu concentration gradient X represented by the following formula (3) is 40 atomic % / nm or less. Ni / Al≦9.00 …(1) Here, the content value of the element expressed as mass% is substituted for the element symbol in formula (1). Cu concentration median C 0 =(C M +C P ) / twenty two) Here, C M is the average Cu concentration (atomic %) in the region where the distance from the interface position to the matrix side is 5 nm or more and 7 nm or less, and C P is the average Cu concentration (atomic %) in the region located at a distance of 5 nm or more and 7 nm or less from the interface position toward the precipitate side. Cu concentration gradient X = (C 1 -C 2 ) / twenty three) Here, C 1 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the matrix side, and C 2 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the precipitate. [2] The copper alloy sheet material according to the above [1], having a tensile strength in the rolling direction of 900 MPa or more. [3] A process of subjecting a cast slab having the above chemical composition to hot rolling, intermediate cold rolling, solution treatment, aging treatment, final cold rolling, and final heat treatment in the above order, Hot rolling is performed under the following conditions: a slab heating temperature of 1000 to 1150°C, a rolling temperature in the final rolling pass of 800°C or higher, a water cooling start temperature of 700°C or higher, a water cooling end temperature of 200°C or lower, and an average cooling rate from the start to the end of water cooling of 30°C / s or higher; The intermediate cold rolling is performed under conditions including 5 or more rolling passes with a total rolling reduction of 80% or more and a rolling reduction of 10% or more per pass; Solution treatment is performed by holding at 950 to 1100°C for 30 seconds or more, and the average cooling rate from 900°C to 300°C is 80°C / s or more. The aging treatment is carried out under the condition that the holding temperature is 400 to 600 °C, provided that when the maximum reaching temperature is 500 °C or higher, the residence time at 500 °C or higher is 8 hours or less. The final cold rolling is carried out under the condition that the total rolling ratio is 45% or more, the rolling passes include 4 or more rolling passes with a rolling ratio of 12% or more per pass, and the outgoing side unit tension is 294 N / mm 2 and includes 4 or more rolling passes with the above conditions. The final heat treatment is carried out under the condition of heating in the temperature range of 300 to 600 °C. A method for manufacturing a copper alloy sheet. Ni / Al ≤ 9.00 …(1) Here, the content value of the corresponding element expressed in mass% is substituted into the position of the element symbol in formula (1). [4] An electronic device component using the copper alloy sheet described in the above [1] or [2] as a material. [5] A conductive spring member using the copper alloy sheet described in the above [1] or [2] as a material. [6] A spring member for an autofocus camera module using the copper alloy sheet described in the above [1] or [2] as a material.
[0013] In this specification, "sheet material" means a sheet-shaped metal material. A thin sheet-shaped metal material may also be called "foil", and such "foil" is also included in the "sheet material" referred to here. A long sheet-shaped metal material wound in a coil shape is also included in the "sheet material". In this specification, the thickness of the sheet-shaped metal material is called "sheet thickness". Also, "sheet surface" means a surface perpendicular to the sheet thickness direction of the sheet material. The sheet surface may also be called "rolling surface". In this specification, the notation "n1~n2" indicating a numerical range means "n1 or more and n2 or less". Here, n1 and n2 are numerical values satisfying n1 < n2.
[0014] The rolling ratio (%) in a certain rolling pass is determined by the following formula (4). Rolling ratio (%) = 100 × (t 0 -t 1 ) / t 0 …(4) t 0: Plate thickness before the rolling pass (mm) t 1 : Plate thickness at the end of the rolling pass (mm) The total rolling ratio (%) in a certain rolling process is determined by the following formula (5). Total rolling ratio (%) = 100 × (h 0 -h 1 ) / h 0 …(5) h 0 : Plate thickness before the first pass of the rolling process (mm) h 1 : Plate thickness at the end of the final rolling pass of the rolling process (mm) Effect of the Invention
[0015] According to the present invention, in a high-strength Cu-Ni-Al-based copper alloy sheet material having a composition range that exhibits a whitish metallic appearance, the heat resistance can be improved significantly compared to the conventional case. [Brief description of the drawings]
[0016] [Figure 1] 1 is a graph illustrating the atomic concentration profiles of the three elements Cu, Ni, and Al perpendicularly penetrating the interface between the parent phase and fine precipitates by three-dimensional atom probe analysis for a Cu-Ni-Al-based copper alloy sheet material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [Chemical composition] Hereinafter, "%" regarding alloy components means "mass %" unless otherwise specified. Ni (nickel) is a major element that constitutes the matrix (parent phase) of Cu-Ni-Al copper alloys together with Cu (copper). In addition, a part of the Ni in the alloy combines with Al to form Ni-Al precipitates (containing Cu), and the fine particles contribute to improving strength. In order to obtain sufficient strength, a Ni content of 10.0% or more is ensured. As the Ni content increases, the alloy exhibits a whiter metallic appearance compared to other general copper alloys. However, like other copper alloys, when exposed to a high humidity environment, a thin oxide film is formed on the metal surface, which may cause noticeable discoloration. In that case, the beautiful white appearance is lost. In particular, when emphasis is placed on discoloration resistance, it is more preferable to increase the Ni content to 12.0% or more and ensure the Al content as described below. On the other hand, as the Ni content increases, hot workability deteriorates. The Ni content is limited to 30.0% or less, and may be controlled to 28.0% or less.
[0018] Al (aluminum) is an element that forms Ni-Al-based precipitates (containing Cu). If the Al content is too low, the strength improvement is insufficient. On the other hand, if the Al content is too high, the hot workability deteriorates. Also, by increasing the Al content along with the increase in the Ni content, the discoloration resistance can be improved. As a result of various investigations, it has been found that the Al content must be in the range of 1.00 to 6.50%, and the Ni / Al ratio must satisfy the following formula (1). From the viewpoint of strength and heat resistance, it is more preferable that the following formula (1)' is satisfied. Ni / Al≦9.0 …(1) 2.0≦Ni / Al≦8.0 …(1)' Here, the content value of the corresponding element expressed as mass % is substituted for the element symbol in formula (1) and formula (1)'.
[0019] Other elements that may be contained as necessary include one or more of Ag (silver), B (boron), Be (beryllium), Co (cobalt), Cr (chromium), Fe (iron), Ga (gallium), Ge (germanium), In (indium), Mg (magnesium), Mn (manganese), Nb (niobium), P (phosphorus), Si (silicon), Sn (tin), Ti (titanium), Zn (zinc), and Zr (zirconium). The content ranges of these optional elements are Ag: 0-0.50%, B: 0-0.15%, Be: 0-0.20%, Co: 0-2.00%, Cr: 0-0.50%, Fe: 0-2.00%, Ga: 0-0.50%, Ge: 0-0.50%, In: 0-0.50%, Mg: 0-0.80%, Mn: 0-2.00%, Nb: 0-0.50%, P: 0-0.20%, Si: 0-1.00%, Sn: 0-2.00%, Ti: 0-2.00%, Zn: 0-2.00%, and Zr: 0-0.40%. From the viewpoint of the cost of the copper alloy, the total content of these optional elements is preferably 5.00% or less, more preferably 4.00% or less, and may be 3.00% or less, or 2.00% or less, or even 1.80% or less.
[0020] The content ranges of these optional elements taking into consideration economy and manufacturability can be Ag: 0-0.45%, B: 0-0.12%, Be: 0-0.15%, Co: 0-1.90%, Cr: 0-0.45%, Fe: 0-1.90%, Ga: 0-0.45%, Ge: 0-0.45%, In: 0-0.45%, Mg: 0-0.60%, Mn: 0-1.80%, Nb: 0-0.45%, P: 0-0.15%, Si: 0-0.80%, Sn: 0-1.90%, Ti: 0-1.90%, Zn: 0-1.90%, and Zr: 0-0.30%.
[0021] The inclusion of elements other than those mentioned above is permitted within a range that does not impede the object of the present invention (ensuring high strength and improving heat resistance). Specifically, the total content of elements other than Ni, Al, Ag, B, Be, Co, Cr, Fe, Ga, Ge, In, Mg, Mn, Nb, P, Si, Sn, Ti, Zn, Zr, and Cu (hereinafter, sometimes referred to as "unspecified elements") is preferably 0.50% or less, and may be controlled to 0.10% or less. The content of unspecified elements can be grasped by quantifying substantially all elements that may be contained in the copper alloy sheet, for example, by the following analytical method.
[0022] (Example of quantitative determination method for alloying elements) O (oxygen) and N (nitrogen) are quantified using an oxygen / nitrogen / hydrogen analyzer (e.g., ONH-836, manufactured by LECO), H (hydrogen) is quantified using a hydrogen analyzer (e.g., EMGA-921, manufactured by Horiba, Ltd.), C (carbon) and S (sulfur) are quantified using a carbon-sulfur analyzer (e.g., CS844, manufactured by LECO), elements of the second to sixth periods (excluding C, N, O, group 17 elements, group 18 elements, Tc (technetium), Po (polonium), and Pm (promethium)) are quantified using ICP-MS (e.g., 7900, manufactured by Agilent), and F (fluorine), Cl (chlorine), and Br (bromine) are quantified using a combustion-ion chromatography apparatus (e.g., DIONEX ICS-1600, manufactured by Thermo Scientific).
[0023] Regarding the chemical composition of the copper alloy sheet material according to the present invention, it can be specified as "consisting of Ni, Al, the optional elements listed above (including cases where the total is 0%), the balance Cu and unavoidable impurities", or it can be specified as "consisting of Ni, Al, the optional elements listed above (including cases where the total is 0% by mass), the unspecified elements listed above (including cases where the total is 0% by mass), the balance Cu".
[0024] [Ultrafine precipitates number density] In order to improve the heat resistance of Cu-Ni-Al-based copper alloy sheets, the number density of ultrafine precipitates with a particle size of 10 to 20 nm must be less than 1.0 × 10 8 pieces / mm 2It is extremely effective to have a high microstructure of 2.6×10 or more, that is, to increase the number density of ultrafine precipitates, especially among fine precipitates. The mechanism by which this improves heat resistance has not been fully elucidated, but when a large number of ultrafine precipitates are dispersed, even if the particle size of these precipitates increases to a certain extent when heated to a temperature range exceeding 500°C, it is believed that there is still a large number of particles that maintain a particle size within the range that contributes to improving strength (for example, 50 nm or less), and this is presumed to significantly suppress the decrease in strength after heating. The number density of ultrafine precipitates is 2.6×10 8 pieces / mm 2 The upper limit of the number density of ultrafine precipitates is not particularly limited, but in the copper alloy having the above-mentioned chemical composition, it is usually 7.0 × 10 8 pieces / mm 2 The range is as follows: The number density of ultrafine precipitates can be determined as follows.
[0025] (How to determine the number density of ultrafine precipitates) Observe the thin film sample using a TEM (transmission electron microscope) and check the L1 2 A dark-field image is obtained using the (1 0 0) diffraction spots of Ni-Al-based precipitates with a regular structure. Of the particles that appear entirely within the field of view of the dark-field image, the number of particles with a particle diameter of 10 nm to 20 nm is counted. Here, the particle diameter is determined by the arithmetic mean of the long and short axis lengths of an ellipse that approximates the particle outline (however, if the ellipse is a perfect circle, the value of the diameter of the circle). This operation is performed for multiple randomly selected non-overlapping fields of view, and the total count number is divided by the total area of the fields of view observed to obtain the number density of ultrafine precipitates (numbers / mm 2 The total area of the observation field is 0.2 μm 2 Calculation of particle size by ellipse approximation and counting of particles with a diameter of 10 nm or more and 20 nm or less can be performed using image processing software.
[0026] [Number density of coarse precipitates] The Cu-Ni-Al-based copper alloy sheet material of the present invention may be subjected to a process of removing unnecessary portions by etching. Reducing the number of coarse precipitates with a major axis of 1.0 μm or more (for example, coarse precipitates with a major axis of 1.0 μm or more and 20.0 μm or less) is effective in forming an etched surface with high smoothness. When etching properties are important, the density of coarse precipitate particles with a major axis of 1.0 μm or more is 3.0×10 4 pieces / mm 2 It is preferable that the value is less than 1.0×10 4 pieces / mm 2 The number density of the coarse precipitates can be determined as follows.
[0027] (How to determine the number density of coarse precipitates) The plate surface was electrolytically polished under the following electrolytic polishing conditions to dissolve only the Cu base material, exposing the precipitate particles, and then ultrasonically cleaned in ethanol for 20 minutes. The surface was then observed with a field emission scanning electron microscope (FE-SEM), and the total number of precipitate particles with a major axis of 1.0 μm or more observed on the FE-SEM image was calculated based on the total observation area (mm 2 ) is the particle number density of the coarse precipitate particles (particles / mm 2 ) Here, the long diameter is the length of the longest line segment connecting any two points on the outer edge of a precipitate particle on the FE-SEM image (however, this line segment must be entirely within the outer edge of the particle). Observations are performed on at least 20 randomly set, non-overlapping fields of view. Precipitate particles that partially protrude from the observation field of view are counted if the long diameter of the portion that appears within the observation field of view is 1.0 μm or more. (Electrolytic polishing conditions) Electrolyte: Distilled water, phosphoric acid, ethanol, and 2-propanol mixed in a volume ratio of 10:5:5:1 Liquid temperature: 20℃ Voltage: 15V ·Electrolysis time: 20 seconds
[0028] [Cu concentration gradient near the matrix / precipitate interface X] In order to improve the heat resistance of Cu-Ni-Al copper alloy sheet materials, in addition to adjusting the number density of ultrafine precipitates as described above, it is important to maintain a microstructure in which the Cu concentration gradient is small near the interface between the parent phase and fine precipitates. Specifically, in the atomic concentration profile of the three elements Cu, Ni, and Al that perpendicularly penetrates the interface between the parent phase (here, the region where the Al concentration is less than 10 atomic % is defined as the parent phase) and fine precipitates with a particle size of 50 nm or less (here, the region where the Al concentration is more than 10 atomic % is defined as the precipitate) by 3D atom probe analysis, the position where the Al concentration is 10 atomic % is defined as the "interface position," and the Cu concentration is the median Cu concentration C in the following formula (2): 0 When the position where (atomic %) is defined as the "Cu concentration median position", it is extremely effective that the Cu concentration gradient X expressed by the following formula (3) is 40 atomic % / nm or less. A more preferable range of the Cu concentration gradient X is 10 atomic % / nm or more and 40 atomic % / nm or less. Cu concentration median C 0 =(C M +C P ) / twenty two) Here, C M is the average Cu concentration (atomic %) in the region where the distance from the interface position to the matrix side is 5 nm or more and 7 nm or less, and C P is the average Cu concentration (atomic %) in the region located at a distance of 5 nm or more and 7 nm or less from the interface position toward the precipitate side. Cu concentration gradient X = (C 1 -C 2 ) / twenty three) Here, C 1 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the matrix side, and C 2 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the precipitate.
[0029] The mechanism by which a small Cu concentration gradient X is effective in improving heat resistance has not yet been fully elucidated, but the following is thought to be the case. In order for precipitates to grow by heating, the interface between the parent phase and the precipitates must move due to atomic diffusion. If the change in atomic concentration near the initial interface is gradual, the rate of atomic diffusion between the parent phase and the precipitates decreases, suppressing the growth rate (coarsening rate) of ultrafine precipitates. As a result, even after heating to a temperature range exceeding 500°C, for example, the number of fine precipitates having a particle size in the range that contributes to strength improvement (for example, 50 nm or less) tends to be maintained in large numbers. In this way, it is considered that in order to improve the heat resistance of the Cu-Ni-Al system copper alloy sheet material, it is extremely effective to increase the number of ultrafine precipitates and to retard the growth (coarsening) of the precipitates when the temperature is raised to a high temperature range by reducing the Cu concentration gradient X.
[0030] FIG. 1 illustrates the atomic concentration profile of three elements, Cu, Ni, and Al, perpendicularly penetrating the interface between the parent phase and fine precipitates with a particle size of 50 nm or less, for the Cu-Ni-Al-based copper alloy sheet material of the present invention, as determined by three-dimensional atom probe analysis. The horizontal axis shows a distance scale based on the position where the Al concentration is 10 atomic % (the "interface position" by definition). In this distance scale, the negative side of the interface position (zero position) is the parent phase side, and the positive side is the precipitate particle side. In this way, a graph with the distance (nm) based on the interface position as the horizontal axis and the atomic concentration (atomic %) as the vertical axis is sometimes referred to as an "atomic concentration profile graph" below. From many observations using a three-dimensional atom probe, it has been confirmed that the composition of the precipitate is approximately 3:1 in atomic ratio (Ni+Cu):Al, and the atomic ratio of Ni and Cu in the precipitate is approximately 6:1, Ni:Cu.
[0031] (How to calculate Cu concentration gradient X) A needle-shaped specimen for atom probe measurement is prepared from the plate sample with the plate thickness direction as the longitudinal direction. A 3D atom probe analysis is performed on the specimen, and based on the obtained 3D data, an analysis line is randomly set that perpendicularly penetrates the interface between the parent phase and the precipitate (the surface with an Al concentration of 10 atomic %). The atomic ratios of Cu, Ni, and Al are obtained along the analysis line, and an atomic concentration profile of the three elements Cu, Ni, and Al is created. In the obtained Cu concentration profile, the average value (atomic %) of the Cu concentration in the region from the interface position (position where the Al concentration is 10 atomic %) to the matrix side at a distance of 5 nm to 7 nm was calculated, and this was defined as the average Cu concentration C M Similarly, the average Cu concentration (atomic %) in the region at a distance of 5 nm or more and 7 nm or less from the interface position to the precipitate side is calculated, and this is defined as the average Cu concentration C P Let us assume that. M and C. P The arithmetic mean value of was calculated using the following formula (2), and this value was taken as the median Cu concentration C 0 (atomic %). The Cu concentration is the median Cu concentration C 0 The position where (atomic %) (the position along the horizontal axis of the atomic concentration profile graph) is the "Cu concentration median position." Cu concentration median C 0 =(C M +C P ) / twenty two) Next, in the Cu concentration profile, the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the matrix side was determined, and this was defined as C 1 Similarly, the Cu concentration (atomic %) at a position 1 nm away from the center of the Cu concentration toward the precipitate was calculated and this was called C 2 (atomic %). Then, the Cu concentration gradient X (atomic % / nm) is calculated using the following formula (3). Cu concentration gradient X = (C 1 -C 2 ) / twenty three) The value "2" in the denominator on the right side of equation (3) represents the concentration C 1 The abscissa position and the concentration C 2 The distance between the corresponding horizontal axis position and the axis is 2 nm. The above operation is carried out for three or more different needle-shaped samples, and the arithmetic mean value of the Cu concentration gradient X obtained from each sample is adopted as the value of the Cu concentration gradient X of the sheet material.
[0032] [Tensile strength] In order to apply the Cu-Ni-Al-based copper alloy sheet material of the present invention to the application of a high-strength current-carrying spring member, the tensile strength in the rolling direction is preferably 900 MPa or more, more preferably 1000 MPa or more. The tensile strength in the rolling direction can be adjusted to, for example, a range of 1300 MPa or more and 1700 MPa or less.
[0033] [Heat resistance] The Cu-Ni-Al-based copper alloy sheet material of the present invention exhibits superior heat resistance compared to conventional materials. Specifically, it exhibits heat resistance such that the 80% hardness maintenance limit temperature measured by the method described in the examples below is, for example, 600°C or higher. The 80% hardness maintenance limit temperature is more preferably 620°C or higher, and even more preferably 650°C or higher. The 80% hardness maintenance limit temperature may be adjusted to be usually in the range of 740°C or lower.
[0034] [Manufacturing method] The copper alloy sheet material described above can be manufactured, for example, by the following manufacturing process. Casting → Hot rolling → Intermediate cold rolling → Solution treatment → Aging treatment → Final cold rolling → Final heat treatment Although not described in the above steps, facing is performed as necessary after hot rolling, and pickling, polishing, or further degreasing is performed as necessary after each heat treatment. Each step will be described below.
[0035] [casting] The cast pieces may be produced by continuous casting, semi-continuous casting, etc. From the viewpoint of preventing oxidation of Al, it is preferable to carry out melting in a chamber under an inert gas atmosphere or under vacuum.
[0036] [Hot rolling] The slab is heated and held at 1000 to 1150°C. It is effective to hold the heating time in this temperature range for 1.5 hours or more, and more preferably for 2 to 5 hours. The slab is then removed from the furnace and subjected to hot rolling. In hot rolling, the rolling temperature of the final pass is 800°C or higher. The temperature of each rolling pass can be expressed by the surface temperature of the material immediately after it leaves the work roll in that rolling pass. The above-mentioned slab heating and hot rolling at 800°C or higher can reduce the amount of coarse second phase (Ni-Al-based precipitate phase) present, and finally, a plate material with a low number density of coarse precipitates can be obtained. On the other hand, in order to easily refine the precipitates in the subsequent process, it is effective to make the cooling rate after the final rolling pass as fast as possible to suppress precipitation during cooling, and in the present invention, forced cooling by water cooling is used. Specifically, the water cooling start temperature is set to 700°C or more, the water cooling end temperature is set to 200°C or less, and the cooling conditions (water volume, line speed, etc.) are controlled so that the average cooling rate from the start of water cooling to the end of water cooling is 30°C / s or more. It is more preferable to control the cooling conditions so that the average cooling rate is 40°C / s or more. The water cooling start temperature is represented by the surface temperature of the material just before the start of water cooling, and the water cooling end temperature is represented by the surface temperature of the material just after the end of water cooling. The average cooling rate from the start of water cooling to the end of water cooling may be adjusted to a range of usually 100°C / s or less. From the viewpoint of stably achieving a final pass rolling temperature of 800°C or more in the operation at the mass production site, the plate thickness after hot rolling (finish plate thickness) is preferably set to a range of, for example, 5 to 20 mm, more preferably 7 to 20 mm.
[0037] [Intermediate cold rolling] The material after hot rolling is subjected to cold rolling. The cold rolling performed at this stage is referred to as "intermediate cold rolling" in this specification. In this intermediate cold rolling, the total rolling reduction must be 80% or more, and more preferably 90% or more. The upper limit of the total rolling reduction is limited according to the capacity of the cold rolling mill used, but it is usually set to a range of 99% or less. In this intermediate cold rolling, it is important to adopt a pass schedule that includes 5 or more rolling passes with a rolling reduction of 10% or more per pass. By repeating such passes under high pressure to ensure a total rolling reduction of 80% or more, the precipitates generated in the hot rolling process are sheared and refined, making it easier to dissolve them in the subsequent solution treatment. Conventionally, in the manufacturing process of Cu-Ni-Al-based copper alloy sheet material, since there has been no need to include 5 or more rolling passes with a rolling ratio of 10% or more per pass in cold rolling applied to hot rolled material, the number of rolling passes with a rolling ratio of 10% or more per pass is generally 4 passes or less at most. In the present invention, a cold rolling mill having sufficient mill power is used to perform strong reduction with a rolling ratio of 10% or more 5 times or more (for example, 5 times or more and 10 times or less).
[0038] [Solution treatment] The material after intermediate cold rolling is subjected to solution treatment under the condition of holding at a temperature range of 950 to 1100 ° C for 30 seconds or more. Since the precipitates are broken and refined by the intermediate cold rolling, the precipitates present in the material can be sufficiently dissolved by the above heating conditions. There is no particular limit to the upper limit of the holding time in the above temperature range, but considering the use of a continuous heat treatment furnace, it is preferable to set it to a range of 360 seconds or less. After the above heating, the material is cooled under conditions where the average cooling rate from 900 ° C to 300 ° C is 80 ° C / s or more, and care is taken to prevent new precipitation from occurring as much as possible during the cooling process. For example, the cooling method can be a method of blowing a cooling gas (such as nitrogen gas) on the surface of the plate material during passing, or water cooling. The average cooling rate from 900 ° C to 300 ° C can be adjusted usually in the range of 80 ° C / s to 150 ° C / s.
[0039] [Aging process] Next, aging treatment is performed to control the generation of precipitates so that a desired structure state in which many ultrafine precipitates are dispersed is obtained after the final heat treatment in the subsequent process. Specifically, the aging holding temperature is set in the range of 400 to 600°C. In addition, when the maximum reaching temperature is 500°C or higher, the residence time at 500°C or higher is limited to 8 hours or less. The residence time in the temperature range of 400 to 600°C can be set in the range of 1 to 75 hours, for example. In the aging treatment, a heat pattern is generally adopted in which after a predetermined temperature is reached, the temperature (i.e., the maximum reaching temperature) is held for a certain period of time, and then cooling is started. In this case, the residence time in the temperature range of 400 to 600°C is longer than the holding time at the maximum reaching temperature, and when the maximum reaching temperature is 500°C or higher, the residence time at 500°C or higher is longer than the holding time at the maximum reaching temperature.
[0040] [Final cold rolling] The material that has undergone aging treatment is subjected to final cold rolling. In this cold rolling, many passes under high pressure and passes under high tension are performed so that the precipitates that have formed during aging can be sheared. Specifically, the total rolling reduction is 45% or more, and the rolling passes include four or more rolling passes with a rolling reduction of 12% or more per pass, and the tension of the delivery unit is 294 N / mm 2 (=30kgf / mm 2 ) or more. A pass schedule including four or more rolling passes with a rolling reduction ratio of at least 60% is more preferable. The upper limit of the total rolling reduction ratio is limited according to the capacity of the cold rolling mill used, but it is usually sufficient to set it within the range of 99% or less. The delivery unit tension is calculated by dividing the tension (N) applied to the material between the work roll and take-up reel of the rolling mill by the cross-sectional area of the material (mm 2 Usually, the number of rolling passes with a rolling reduction rate of 12% or more per pass can be adjusted within the range of 4 to 8, and the exit unit tension is 294 N / mm 2The number of rolling passes may be adjusted within the range of 4 to 8. A rolling pass schedule that follows such conditions allows fine precipitates to be sufficiently sheared. This shearing of the precipitates can increase the number density of ultrafine precipitates, and also reduce the above-mentioned "Cu concentration gradient X" near the interface between the parent phase and the precipitates (make the concentration change more gradual).
[0041] [Final heat treatment] Next, the final heat treatment is performed by heating to a temperature range of 300 to 600°C. This heat treatment is extremely effective in increasing the strength that tends to decrease due to the final cold rolling. When heated to 300 to 600°C, a part of Ni is replaced with Cu, resulting in Ni 3 Al phase (L1 2 It is believed that the degree of order in the structure increases, and as a result, the precipitation strengthening ability is restored, which contributes to the improvement of strength. The holding time at 300 to 600°C is preferably set in the range of 10 to 15,000 seconds, and from the viewpoint of economic efficiency, the holding time is more preferably 10 to 600 seconds. When this final heat treatment is performed, the Cu concentration gradient X tends to increase, but is maintained within the above-mentioned specified range. As a result, a plate material that combines high strength and excellent heat resistance is realized.
[0042] [Electronic equipment parts] The plate material according to the present invention obtained as described above has excellent strength and heat resistance, and therefore can be used as a material for suitably manufacturing electronic device parts, such as conductive spring members such as lead frames, connectors, and leaf springs for autofocus camera modules, and non-magnetic high-strength members.
[0043] [Conductive spring material] A conductive spring member having excellent strength and heat resistance can be obtained by processing such as press punching, bending, and etching using the plate material according to the present invention. This conductive spring member can be used, for example, as a spring member for an autofocus camera module. An example of the autofocus camera module is one having a configuration including a lens, a driving force applying means for driving the lens in the optical axis direction, and the conductive spring member for biasing the lens to a reference position in the optical axis direction. EXAMPLES
[0044] Copper alloys having the chemical compositions shown in Table 1 were melted and cast using a vertical semi-continuous casting machine. The analysis samples taken from the cast pieces were subjected to elemental analysis using the method described in the above-mentioned "Example of a method for quantifying alloying elements." As a result, in all examples, the total content of elements other than Ni, Al, Ag, B, Be, Co, Cr, Fe, Ga, Ge, In, Mg, Mn, Nb, P, Si, Sn, Ti, Zn, Zr, and Cu was 0.10% or less.
[0045] The resulting slab was heated and held for the temperature and time shown in Table 2, then extracted, hot rolled, and water-cooled. The water-cooling start temperature was 700°C or higher, and the water-cooling end temperature was 200°C or lower. The total hot-rolling reduction was 79-94%. The rolling temperature of the final pass, the average cooling rate from the start to the end of water-cooling, and the finished plate thickness after hot rolling are shown in Table 2. In some cases (No. 32, 33, 35) where cracks occurred during hot rolling, production was discontinued at that point. After hot rolling, the surface oxide layer was removed by mechanical polishing (face milling), and intermediate cold rolling was performed under the conditions shown in Table 2. The column "Number of passes with rolling reduction ratio ≧10%" in Table 2 lists the number of rolling passes with a rolling reduction ratio of 10% or more per pass.
[0046] Next, solution treatment was performed under the conditions shown in Table 2 using a continuous annealing furnace equipped with a heating zone and a forced cooling zone. In the forced cooling zone, forced cooling was performed by blowing nitrogen gas forcedly circulated by a fan onto the surface of the plate during passing. The cooling rate can be controlled by adjusting the strength of the convection. During passing, the material surface temperature T 0 (℃) and the material surface temperature T immediately after the forced cooling 1 (℃) was measured. 0 is 900℃ or more, and T 1 It was confirmed that the temperature was 300°C or less. 0 , T 1 Based on the cooling curve determined from the sheet passing speed and the temperature at which the sheet was cooled, the average cooling rate from 900°C to 300°C was determined.
[0047] After the solution treatment, the steel sheets were directly subjected to aging treatment under the conditions shown in Table 2 without applying cold rolling strain. The aging treatment was performed using a batch-type annealing furnace at a maximum temperature of T M After heating to (℃), the temperature T M The temperature was kept at T for a specified time. M In the cases where the temperature exceeded 500°C, the heat pattern used was such that the residence time at 500°C or higher was the value shown in Table 2. The atmosphere was nitrogen. Then, final cold rolling was performed under the conditions shown in Table 3 to obtain the final plate thickness shown in the same table. The number of passes with a rolling reduction of 12% or more is shown in the "Number of passes with a rolling reduction of 12% or more" column in Table 3, and the number of passes with a rolling reduction of 12% or more is shown in the "Delivery unit tension ≥ 294 N / mm 2 The "Number of passes" column shows that the tension of the exit unit is 294N / mm 2 (=30kgf / mm 2 ) or more are listed. Then, the final heat treatment was performed in a nitrogen atmosphere. The holding temperature and holding time are shown in Table 3. No. 16 was annealed in a batch annealing furnace, and the others were annealed in a continuous annealing furnace.
[0048] In this manner, plate products (test materials) were obtained having the final plate thicknesses shown in Table 3. The following investigations were carried out on each test material.
[0049] (number density of ultrafine precipitates) According to the above "How to determine the number density of ultrafine precipitates", L1 2 The number density (number / mm ) of ultrafine precipitates with a particle size of 10 to 20 nm was determined from the dark-field image using the (1 0 0) diffraction spots of the ordered structure. 2 ) was obtained. The TEM used was an EM-2010 manufactured by JEOL Ltd. Samples for TEM observation were prepared by mechanically polishing and buffing the plate surface (rolled surface) of the test material to a thickness of about 30 μm, and then thinning it by ion milling. However, test materials with a thickness as thin as about 30 μm were directly subjected to ion milling. The magnification of the dark field image was 50,000 times. Measurement of particle size and counting of the number of particles with particle sizes within a specified range were performed on images processed with a threshold value of 105-255 using image analysis software ImageJ (National Institutes of Health (NIH), Version 1.52a).
[0050] The analysis conditions using this software are as follows: on the "Set Scale" screen, which is displayed by selecting Analyze and Set Scale in sequence, measure the number of pixels of the scale bar length of the TEM dark-field image taken and enter it into Distance in pixels. Next, the length of the scale bar (nm) is entered into Known distance, the Pixel aspect ratio is set to 1.0, and the Unit of length is set to nm, so that the size of the precipitates can be recognized on the software. After that, the Crop function is used to leave an analysis area of 240 nm × 240 nm, and the remaining part is deleted. At this time, in the TEM dark-field image before the analysis area is cut out, there may be areas where the precipitates are not reflected on the dark-field image even though they exist due to the warping or thickness variation of the TEM observation sample. In such cases, the areas where the precipitates are not reflected are avoided and the areas where the precipitates are reflected are selected as the analysis area.
[0051] After setting this scale and deleting the area other than the analysis area, the upper limit of the threshold was set to 255 and the lower limit to 105 in the "Threshold" screen displayed by selecting Image, Adjust, and Threshold in sequence, and the area where the precipitate particles existed was binarized and identified. Then, the "Fit Ellipse" item was checked in the "Set Measurements" screen, and particle analysis was performed with Circularity set to 0.00-1.00 in the "Analyze Particles" screen of the same software. For each particle in the obtained analysis data, the average value of the Major (long axis) and Minor (short axis) values was calculated and used as the particle size of the particle. The number of particles with a particle size of 10 nm to 20 nm was counted and divided by the area of the analysis area to calculate the number density of ultrafine precipitate particles with a particle size of 10 to 20 nm. The above-mentioned number density of ultrafine precipitate particles was calculated for the dark-field images of five fields of view, and the average value of the obtained values was taken as the number density of ultrafine precipitate particles for the sample.
[0052] (Cu concentration gradient X near the matrix / precipitate interface) According to the above-mentioned "How to obtain Cu concentration gradient X", three needle-shaped samples were prepared from the test material, and Cu concentration gradient X (atomic % / nm) was obtained from the obtained Cu concentration profile. The three-dimensional atom probe field ion microscope used was a LEAP-4000HR manufactured by AMETECH. The needle-shaped samples were prepared by the focused ion beam processing method so that the plate thickness direction of the test material was the longitudinal direction of the needle. The measurement was performed at a temperature of 150K. The size of the analysis area by the three-dimensional atom probe was: length: 200nm, tip: a circle with a diameter of 10nm in the cross section perpendicular to the longitudinal direction of the sample, and base: a circle with a diameter of 30nm in the cross section perpendicular to the longitudinal direction of the sample. The slope of the Cu concentration profile at the matrix / precipitate interface (the above-mentioned Cu concentration gradient X) was calculated using the analysis software: IVAS and the analysis method: Maximum separation method. The plot interval of the element concentration profile was 10 points per nm (i.e., 0.1 nm intervals).
[0053] (Number density of coarse precipitates) The number density of coarse precipitates with a major axis of 1.0 μm or more was determined from FE-SEM images according to the above-mentioned "Method for determining the number density of coarse precipitates". The FE-SEM used was a JSM-7200F manufactured by JEOL Ltd.
[0054] (Tensile strength) Tensile test pieces (JIS No. 13 B) in the rolling direction (LD) were taken from the test material, and tensile tests were performed according to JIS Z2241 with the number of tests being n = 5 to measure the tensile strength. The average value of n = 5 was taken as the performance value of the test material.
[0055] (Limit temperature at which 80% hardness is maintained) A small sample cut from the test material was placed in a furnace heated to a predetermined temperature in 20°C increments in the range from 400°C to 800°C, and was heat-treated by holding the temperature for 1 hour, then removing it from the furnace and cooling it in water. For each test material, the Vickers hardness (JIS Z2244:2009) of the plate surface of the test material sample before heat treatment and the sample heat-treated at each set temperature was measured with a load of 100g, and the measurement data was plotted on an orthogonal coordinate system with the heat treatment temperature (°C) on the horizontal axis and the Vickers hardness (HV) on the vertical axis to create a softening curve. The Vickers hardness measurement was performed by polishing the surface of the test material using a grinding wheel (manufactured by Bosch Corporation, DREMEL MICRO) in the order of #600 and #1000 to remove the surface oxide film, and then measuring at seven points. The average value of the five points excluding the maximum and minimum values was adopted as the hardness of the test material. The hardness of the test material before heat treatment was H 0 (HV), 0.8H 0 The temperature at the intersection of the straight line representing the hardness and the softening curve was defined as the "80% hardness maintenance limit temperature". In Cu-Ni-Al-based copper alloy sheet materials, those having the above-mentioned 80% hardness maintenance limit temperature of 600°C or more can be evaluated as having a significant improvement in heat resistance compared to conventional high-strength Cu-Ni-Al-based copper alloy sheet materials. Therefore, those having an 80% hardness maintenance limit temperature of 600°C or more were judged to pass. The test results are shown in Table 3.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] All of the Cu-Ni-Al-based copper alloy sheets of the present invention had a high number density of ultrafine precipitates and a small Cu concentration gradient X near the matrix / precipitate interface, and were excellent in heat resistance. They also had high strength levels. In addition, the number density of coarse precipitates that may adversely affect etching properties was very low.
[0060] In contrast, the comparative example No. 31 had an excessively low Ni content, and No. 34 had an excessively low Al content, resulting in a small number of ultrafine precipitates, a low strength level, and no improvement in heat resistance. No. 32 had too much Ni content, No. 33 had too much Al content, and No. 35 was a slab that had been heated at too high a temperature. As a result, cracks occurred during hot rolling and the slab could not be processed further. In No. 36, the cooling rate after the final pass of hot rolling was too slow, so the number of ultrafine precipitates was reduced and the Cu concentration gradient X near the matrix / precipitate interface became large, and the heat resistance was not improved. In this example, the number density of ultrafine precipitates was low, but the strength level was high. This is thought to be because the contents of Ni and Al, which are the main elements of Ni-Al-based precipitates, were sufficiently secured, so that fine precipitates that contribute to strength, for example, about 50 nm or less, were sufficiently formed, although they are not as small as ultrafine precipitates. This point is the same for Nos. 37 to 40 below. In No. 37, the number of rolling passes in which the rolling reduction rate per pass was 10% or more was insufficient in the intermediate cold rolling, so that the final amount of ultrafine precipitates was reduced and the Cu concentration gradient X near the matrix / precipitate interface became large, and the heat resistance was not improved. No. 38 had a tension of 294N / mm on the delivery unit during final cold rolling. 2 Since the number of rolling passes was insufficient, the number of ultrafine precipitates was ultimately reduced and the Cu concentration gradient X near the matrix / precipitate interface became large, so that the heat resistance was not improved. Nos. 39 and 40 are manufactured under the conventional manufacturing conditions of Cu-Ni-Al-based copper alloy sheets. The cooling rate after the final pass of hot rolling is slower than that specified in the present invention, the number of rolling passes in which the rolling reduction rate per pass is 10% or more in the intermediate cold rolling is less than that specified in the present invention, and the tension of the delivery unit in the final cold rolling is 294 N / mm 2 The number of rolling passes, which is equal to or greater than the number specified in the present invention, is smaller than that specified in the present invention. In addition, the temperature of the solution treatment in No. 40 is lower than that specified in the present invention. In all of these cases, the final amount of ultrafine precipitates was reduced, and the Cu concentration gradient X in the vicinity of the matrix / precipitate interface was increased, resulting in inferior heat resistance compared to the examples of the present invention.
Claims
1. In mass%, Ni: 10.0 to 30.0%, Al: 1.00 to 6.50%, Ag: 0 to 0.50%, B: 0 to 0.15%, Be: 0 to 0.20%, Co: 0 to 2.
00. %, Cr: 0-0.50%, Fe: 0-2.00%, Ga: 0-0.50%, Ge: 0-0.50%, In: 0-0.50%, Mg: 0-0.80%, Mn: 0-2. 00%, Nb: 0-0.50%, P: 0-0.20%, Si: 0-1.00%, Sn: 0-2.00%, Ti: 0-2.00%, Zn: 0-2.00%, Zr: 0-0.40%, and the balance being Cu and unavoidable impurities, and has a chemical composition that satisfies the following formula (1), and the number density of ultrafine precipitates having a particle diameter of 10-20 nm is 1.0×10 8 pieces / mm 2 In the atomic concentration profile of the three elements Cu, Ni, and Al perpendicularly penetrating the interface between the parent phase (region where the Al concentration is less than 10 atomic %) and the fine precipitates (region where the Al concentration is more than 10 atomic %) having a particle size of 50 nm or less by three-dimensional atom probe analysis, the position where the Al concentration is 10 atomic % is defined as the "interface position", and the Cu concentration is the Cu concentration median value C 0 When the position where (atomic %) is defined as the "Cu concentration median position", the Cu concentration gradient X represented by the following formula (3) is 40 atomic % / nm or less. Ni / Al≦9.00…(1) Here, the content value of the element expressed as mass % is substituted for the element symbol in formula (1). Cu concentration median C 0 = (C M +C P ) / 2 … (2) Here, C M is the average Cu concentration (atomic %) in the region at a distance of 5 nm or more and 7 nm or less from the interface position to the parent phase side, C P is the average Cu concentration (atomic %) in the region located at a distance of 5 nm or more and 7 nm or less from the interface position toward the precipitate side. Cu concentration gradient X=(C 1 -C 2 ) / 2 … (3) Here, C 1 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the matrix side, C 2 is the Cu concentration (atomic %) at a position 1 nm away from the center position of the Cu concentration toward the precipitate side.
2. 2. The copper alloy sheet material according to claim 1, having a tensile strength in the rolling direction of 900 MPa or more.
3. In mass percent, Ni: 10.0-30.0%, Al: 1.00-6.50%, Ag: 0-0.50%, B: 0-0.15%, Be: 0-0.20%, Co: 0-2.00%, Cr: 0-0.50%, Fe: 0-2.00%, Ga: 0-0.50%, Ge: 0-0.50%, In: 0-0.50%, Mg: 0-0.80%, Mn: 0-2.00%, Nb: 0-0. 50%, P: 0-0.20%, Si: 0-1.00%, Sn: 0-2.00%, Ti: 0-2.00%, Zn: 0-2.00%, Zr: 0-0.40%, the balance being Cu and unavoidable impurities, and the chemical composition of the cast slab satisfies the following formula (1): Hot rolling is performed under the following conditions: a slab heating temperature of 1000 to 1150°C, a rolling temperature in the final rolling pass of 800°C or higher, a water cooling start temperature of 700°C or higher, a water cooling end temperature of 200°C or lower, and an average cooling rate from the start of water cooling to the end of water cooling of 30°C / s or higher; The intermediate cold rolling is performed under conditions including 5 or more rolling passes with a total rolling reduction of 80% or more and a rolling reduction of 10% or more per pass; The solution treatment is performed under the condition that the temperature is kept at 950 to 1100 ° C for 30 seconds or more and the average cooling rate from 900 ° C to 300 ° C is 80 ° C / s or more, Aging treatment is performed at a holding temperature of 400 to 600°C, but if the maximum temperature is 500°C or higher, the residence time at 500°C or higher is 8 hours or less. The final cold rolling includes four or more rolling passes with a total rolling reduction of 45% or more and a rolling reduction of 12% or more per pass, and the tension of the delivery unit is 294 N / mm 2 The rolling is performed under conditions including four or more rolling passes. The final heat treatment is performed at a temperature of 300 to 600°C. A method for manufacturing copper alloy sheet material. Ni / Al≦9.00…(1) Here, the content value of the element expressed as mass % is substituted for the element symbol in formula (1).
4. 3. An electronic device part using the copper alloy sheet material according to claim 1 or 2 as a material.
5. A conductive spring member using the copper alloy sheet material according to claim 1 or 2 as a material.
6. 3. A spring member for an autofocus camera module, comprising the copper alloy sheet material according to claim 1 or 2.
Citation Information
Patent Citations
Cu-Ni-Al-BASED COPPER ALLOY SHEET MATERIAL, MANUFACTURING METHOD THEREOF, AND CONDUCTIVE SPRING MEMBER
JP2019002042A
Cu-Ni-Al-BASED COPPER ALLOY SHEET MATERIAL, MANUFACTURING METHOD THEREFOR, AND CONDUCTIVE SPRING MEMBER
JP2020050923A
HIGH YOUNG Cu-Ni-Al-BASED COPPER ALLOY SHEET, METHOD FOR PRODUCING THE SAME, AND CONDUCTIVE SPRING MEMBER
JP2020079436A
Cu-Ni-Al SYSTEM COPPER ALLOY PLATE MATERIAL, MANUFACTURING METHOD THEREOF AND CONDUCTIVE SPRING MEMBER
JP2022027545A
Cu-Ni-Al-BASED COPPER ALLOY SHEET MATERIAL, MANUFACTURING METHOD THEREOF, AND CONDUCTIVE SPRING MEMBER
JP2022115695A